Rebel souls : Walt Whitman and America's first Bohemians - Martin, Justin (Boston, MA : Da Capo Press, a member of the Perseus Books Group, 2014)
"In the shadow of the Civil War, a circle of radicals in a rowdy saloon changed American society and helped set Walt Whitman on the path to poetic immortality. Rebel Souls is the first book ever written about the colorful group of artists-- regulars at Pfaff's Saloon in Manhattan-- rightly considered America's original Bohemians. Besides a young Whitman, the circle included actor Edwin Booth; trailblazing stand-up comic Artemus Ward; psychedelic drug pioneer and author Fitz Hugh Ludlow; and brazen performer Adah Menken, famous for her Naked Lady routine. Central to their times, the artists managed to forge connections with Ralph Waldo Emerson, Mark Twain, and even Abraham Lincoln. Justin Martin shows how this first bohemian culture--imported from Paris to a dingy Broadway saloon--seeded and nurtured an American tradition of rebel art that thrives to this day."--
A visit to Pfaff's -- Bohemia crosses the Atlantic -- A long table in a vaulted room -- Whitman at a crossroads -- Hashish and Shakespeare -- Bold women and Whitman's beautiful boys -- The Saturday Press -- Leaves, third edition -- Year of meteors -- Becoming Artemus Ward -- "The heather is on fire" -- Whitman to the front -- Bohemia goes West -- The soldiers' missionary -- Twain shall they meet -- "O heart! heart! heart!" -- A brief revival -- All fall down -- "Those times, that place."
"A Merloyd Lawrence book."
Includes bibliographical references (pages 277-315) and index.
Keywords: Whitman, Walt, -- 1819-1892 -- Friends and associates; Bohemianism -- New York (State) -- New York -- History -- 19th century; New York (N.Y.) -- Intellectual life -- 19th century; Ward, Artemus, -- 1834-1867.; Booth, Edwin, -- 1833-1893.; Ludlow, Fitz Hugh, -- 1836-1870.; Menken, Adah Isaacs, -- 1835-1868.; Bars (Drinking establishments) -- New York (State) -- New York -- History -- 19th century; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; POETRY -- American -- General; Booth, Edwin, -- 1833-1893; Ludlow, Fitz Hugh, -- 1836-1870; Menken, Adah Isaacs, -- 1835-1868; Ward, Artemus, -- 1834-1867; Whitman, Walt, -- 1819-1892; Bars (Drinking establishments); Bohemianism; Friendship; Intellectual life; New York (State) -- New York; 1800 - 1899; History